2016
DOI: 10.1080/17550874.2016.1264017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shrub browsing by mountain hare and reindeer in subarctic Sweden

Abstract: Background: Climate warming has been causing an increase in tall shrub cover around the Arctic, however, mammalian herbivory has been shown to inhibit shrub expansion. Though the effect of reindeer (Rangifer tarandus) and many other mammals has been widely studied in this context, the role of the mountain hare (Lepus timidus) in subarctic Scandinavia remains unknown. Aims: To quantify browsing from mountain hare and reindeer on tall shrubs in different vegetation types and to investigate differences in shrub p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Growing season TDD were significantly higher in ambient plots and there was a significant negative correlation between mean shrub height and TDD at the reindeer-grazed heath sites, which is most likely an effect of increased shading. Although rodents and hares, which have been found to exert a strong browsing pressure on B. nana (Vowles et al 2016), were not prevented from accessing the exclosures, the exclusion of large herbivores had a significant effect on both shrub height and cover of tall shrubs at our sites. This suggests that even though the effect on ericoid shrub species was minor, reindeer browsing of tall, deciduous shrubs, could still impact key ecosystem functions such as shading, with knock-on effects for soil temperature and nutrient cycling.…”
Section: Exclmentioning
confidence: 82%
“…Growing season TDD were significantly higher in ambient plots and there was a significant negative correlation between mean shrub height and TDD at the reindeer-grazed heath sites, which is most likely an effect of increased shading. Although rodents and hares, which have been found to exert a strong browsing pressure on B. nana (Vowles et al 2016), were not prevented from accessing the exclosures, the exclusion of large herbivores had a significant effect on both shrub height and cover of tall shrubs at our sites. This suggests that even though the effect on ericoid shrub species was minor, reindeer browsing of tall, deciduous shrubs, could still impact key ecosystem functions such as shading, with knock-on effects for soil temperature and nutrient cycling.…”
Section: Exclmentioning
confidence: 82%
“…Ungulates hampered ecological succession, halted shrub encroachment and consequently affected negatively above‐ground carbon stocks of the shrub understorey. Reductions in shrub biomass and in shrub carbon stocks have been observed in other ecosystems browsed by wild ungulates in North America (e.g., mule deer Odocoileus hemionus (Huffman & Moore, ); wapiti Cervus canadensis , pronghorn Antilocapra americana , and mule deer Odocoileus hemionus (Singer & Renkin, )) and Europe (e.g., reindeer Rangifer tarandus ; Vowles, Molau, Lindstein, Molau, & Björk, ); roe deer Capreolus capreolus , and red deer Cervus elaphus (González Hernández & Silva‐Pando, ). Our results also showed that ungulate browsing significantly reduced the accumulation of twigs and leaves in litter, and therefore litter carbon stocks.…”
Section: Discussionmentioning
confidence: 83%
“…In this region, the winter is the season that is warming the most (Scharn, Brachmann, et al, 2021 ), which most likely does not affect birch growth itself, but may influence snow conditions. The thickness, continuity and duration, of the winter snowpack are common limiting factors for arctic vegetation as the snow provides shelter from the harsh winter climate (Wipf & Rixen, 2010 ), as well as protection from large herbivores such as mountain hare, ptarmigan, and reindeer (Christie et al, 2014 ; Nordengren et al, 2003 ; Rödel et al, 2004 ; Vowles et al, 2016 ). Browsing may have played a significant role in controlling birch growth (Kaarlejärvi et al, 2013 ; Løkken et al, 2019 ; Speed et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The area is grazed by mountain hare ( Lepus timidus ), rock ptarmigan ( Lagopus mutus ), lemming ( Lemmus lemmus ), and semi‐domesticated reindeer ( Rangifer tarandus ). Reindeers graze in the area from July to September with a density of approximately 2.3 reindeers/km 2 (Vowles et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%